1992
DOI: 10.1042/cs0820521
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vascular responses and thermoregulation in relation to age

Abstract: 1. Sympathetic vasoconstrictor responses to inspiratory gasp and contralateral arm cold challenge were assessed in fingertip skin in relation to age and were correlated with vasoconstrictor ability during body cooling. The above relationship was also examined in diabetic patients in whom vasoconstrictor responses to inspiratory gasp and contralateral arm cold challenge had been shown previously to be markedly impaired. 2. Vasoconstrictor responses to inspiratory gasp and contralateral arm cold challenge, measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 15 publications
1
63
0
1
Order By: Relevance
“…Elderly people are more susceptible to changes in weather conditions than the young. 19 The low temperature-related higher incidence of OHCA in the elderly might be partly explained by the age-dependent decline in homeostasis, as reported by Khan et al 34 The higher incidence of arterial disease in the elderly may also make them more susceptible to thrombosis. 33 The Eurowinter Group noted that winter mortality from heart disease could be reduced by wearing warmer clothes.…”
Section: Discussionmentioning
confidence: 72%
“…Elderly people are more susceptible to changes in weather conditions than the young. 19 The low temperature-related higher incidence of OHCA in the elderly might be partly explained by the age-dependent decline in homeostasis, as reported by Khan et al 34 The higher incidence of arterial disease in the elderly may also make them more susceptible to thrombosis. 33 The Eurowinter Group noted that winter mortality from heart disease could be reduced by wearing warmer clothes.…”
Section: Discussionmentioning
confidence: 72%
“…Venous occlusion plethysmography measurements of forearm blood flow are more dependent on muscle blood flow than skin blood flow during normothermic conditions (3). Therefore, it is unknown whether similar agerelated alterations in vasoconstriction occur in the cutaneous vasculature.Previous studies have observed increased convective heat loss and higher skin temperatures in the elderly during cold stress (15,18,31). This greater heat loss is not attributed to decreases in fitness but rather to the inability to reduce skin temperatures to the same degree in older compared with young subjects (1, 6).…”
mentioning
confidence: 93%
“…Previous studies have observed increased convective heat loss and higher skin temperatures in the elderly during cold stress (15,18,31). This greater heat loss is not attributed to decreases in fitness but rather to the inability to reduce skin temperatures to the same degree in older compared with young subjects (1, 6).…”
mentioning
confidence: 93%
“…Vasoconstriction and shivering, which are the primary means of maintaining body temperature during exposure to cold, are less efficient with this decline in vitality 29,30 . In normal aging, such changes are part of the overall framework of physiological changes.…”
Section: Discussionmentioning
confidence: 99%